Ефективні технологічні модулі як елемент реструктуризації металургійного підприємства - Смірнов, Ю.О. (Physico-technological Institute of Metals and Alloys, 2023)
At present, the defining trends in the developed metallurgical countries of the world are characterized by an important feature for the rapid expansion of the brand composition of high-quality and alloyed steel grades. Global leaders in the steel industry are increasingly building up their competitive advantages in terms of innovation in efficient processes and new product. It is widely known that the world steel market has experienced serious production growth in the last decade. So, in 2002 its production reached the level of 895 million tons, and in 2019 exceeded 1.8 billion tons. It should be noted that the tendency to increase production volumes is achieved mainly due to countries such as China, India and Iran. The modern metallurgical industry is a definite cumulative system of highly efficient technologies, which are based on a small number of powerful technological paradigms embodied in reliable technological processes. These technological processes and systems reached their peak at the end of the 20th – beginning of the 21st centuries. Currently, they allow us to produce almost the entire range of high-quality steel grades at a fairly low price, which are in demand on the market by various industries. Meanwhile, the efficiency of the functioning of these technological processes is associated with a number of physical restrictions, which include, first of all, high specific energy consumption per 1 ton of steel, high requirements for the iron content in sinter and pellets, and constantly increasing requirements for harmful emissions into the environment etc.